Organizational climate of kindergartens and teacher professional learning: mediating effect of teachers’ collective efficacy and moderating effect of mindfulness in teaching - Hao, Shuang; Yu, Dongqing; Fu, Lisha (Frontiers in Psychology, 2024)
Introduction: This study was aimed at testing a moderated mediation model of teaching mindfulness and teachers’ collective efficacy in the relationships between the organizational climate of kindergartens and teacher professional learning. Methods: A sample of 1095 kindergarten teachers completed self-report questionnaires assessing their perceptions of the organizational climate of kindergartens, collective efficacy, teaching mindfulness, and professional learning. Results: Controlling for teaching experience and kindergarten level, the results show that kindergarten organizational climate significantly and positively predicted teacher professional learning and the collective efficacy of teachers played a partial mediating role between them. Furthermore, moderation analysis revealed that teaching mindfulness moderated the relationship between kindergarten organizational climate and teacher professional learning. Discussion: These results expand our understanding of how the organizational climate of kindergartens affects teacher professional learning. In practice, professional learning of kindergarten teachers can be facilitated by creating an open organizational climate and improving their ability to perceive the collective.Furthermore, the moderating role of teaching mindfulness suggests that intervening in teachers' teaching mindfulness possibly is an influential way to maximize the impact of kindergarten organizational climate on professional learning.